Von Willebrand factor in patients on mechanical circulatory support – a double-edged sword between bleeding and thrombosis - Hudzik, Bartosz; Kaczmarski, Jacek; Pacholewicz, Jerzy; Zakliczynski, Michal; Gasior, Mariusz; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Mechanical circulatory support (MCS) is an umbrella term describing the various technologies used in both short- and long-term management of patients with either end-stage chronic heart failure (HF) or acute HF. Most often, MCS has emerged as a bridge to transplantation, but more recently it is also used as a destination therapy. Mechanical circulatory support includes left ventricular assist device (LVAD) or bi-ventricular assist device (Bi-VAD). Currently, 2- to 3-year survival in carefully selected patients is much better than with medical therapy. However, MCS therapy is hampered by sometimes life-threatening complications including bleeding and device thrombosis. Von Willebrand factor (vWF) has two major functions in haemostasis. First, it plays a crucial role in platelet-subendothelium adhesion and platelet-platelet interactions (aggregation). Second, it is the carrier of factor VIII (FVIII) in plasma. Von Willebrand factor prolongs FVIII half-time by protecting it from proteolytic degradation. It delivers FVIII to the site of vascular injury thus enhancing haemostatic process. On one hand, high plasma levels of vWF have been associated with an increased risk of thrombosis. On the other, defects or deficiencies of vWF underlie the inherited von Willebrand disease or acquired von Willebrand syndrome. Here we review the pathophysiology of thrombosis and bleeding associated with vWF.